A public health study on the participation mechanism of social capital in the governance of public sports space in dilapidated urban communities - a case study of Changsha City, Hunan Province - Li Xinze; Zhang Xiaoyi; He Qiao (Frontiers Media S.A., 2023)
IntroductionChina's aging population, mobile population, low-income families, and other vulnerable groups congregate in dilapidated urban communities serving as public health spaces. As a result, managing public sports spaces in aging urban areas is a significant public health project in China, an essential strategy for raising residents' quality of life, and a significant effort to support the active aging of the older adult.MethodsThe study used mathematical and statistical techniques, questionnaires, and logical deduction to conduct a public health study on the participation mechanism of social capital in the governance of public sports spaces in dilapidated urban communities. It chose 11 old Changsha, Hunan Province, communities as the research objects.ResultsPersonal social capital was found to boost the availability of public sports spaces in older populations through social connections. Collective social capital improves the availability of public sports spaces in aging populations through social trust and stabilizes the order of public sports spaces in aging communities through social involvement.DiscussionTo improve the governance efficiency of public sports spaces in aging urban communities, the study aims to actively mobilize and accumulate social capital through cultivating the public spirit, reshaping the concept of sports governance, appropriately decentralizing and empowering, strengthening sports governance structures, enhancing communication and collaboration, and building sports governance. This is essential for China to fully implement the policies of active aging, a healthy China, and creating a community for global public health.